Bernd Zimmermann (1946-2018) - Ambrus, András (Teaching Mathematics and Computer Science, 2018)
Our great friend, the always helpful supporter of the Hungarian mathematics didactics, Bernd Zimmermann, the retired mathematics didactics professor of Friedrich Schiller University of Jena, passed away on 19th of July 2018. After a short chronology of his life, we remember some of the many areas of his work with strong Hungarian connections.